2015
DOI: 10.1128/aac.00316-15
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Antibiotic-Induced Oxidative Stress Responses between Laboratory and Clinical Isolates of Streptococcus pneumoniae

Abstract: Oxidants were shown to contribute to the lethality of bactericidal antibiotics in different bacterial species, including the laboratory strain Streptococcus pneumoniae R6. Resistance to penicillin among S. pneumoniae R6 mutants was further shown to protect against the induction of oxidants upon exposure to unrelated bactericidal compounds. In the work described here, we expanded on these results by studying the accumulation of reactive oxygen species in the context of antibiotic sensitivity and resistance by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The decreased ROS concentrations in adapted cells could also promote the development of resistance through ROS-induced mutagenesis (25), as ROS induced by bactericidal antibiotics have been shown to result in oxidation of the nucleotide pool (26,27). Similar results were obtained in a Streptococcus pneumoniae strain resistant to either penicillin, ciprofloxacin, or kanamycin (28). In contrast to wild-type S. pneumoniae, cells resistant to one of those three bactericidal antibiotics did not respond by producing ROS upon exposure to another.…”
Section: Discussionmentioning
confidence: 57%
“…The decreased ROS concentrations in adapted cells could also promote the development of resistance through ROS-induced mutagenesis (25), as ROS induced by bactericidal antibiotics have been shown to result in oxidation of the nucleotide pool (26,27). Similar results were obtained in a Streptococcus pneumoniae strain resistant to either penicillin, ciprofloxacin, or kanamycin (28). In contrast to wild-type S. pneumoniae, cells resistant to one of those three bactericidal antibiotics did not respond by producing ROS upon exposure to another.…”
Section: Discussionmentioning
confidence: 57%
“…However, the higher levels of Mn-superoxide dismutase was detected in the GacS mutant (Kang et al, 2004). These findings suggest that the Gac/Rsm regulon helps PcO6 survive under oxidative stress and other unfavorable environments, such as when challenged by antibiotics produced by other microbes (Dridi et al, 2015).…”
Section: Gac/rsm System a Master Switch For Global Regulationmentioning
confidence: 62%
“…However, for the Bcc strains tested we could not find a correlation between the MIC and the production of ROS. Dridi et al (2015) found that whether or not resistance led to a decreased ROS production in clinical isolates of Streptococcus pneumoniae differed between laboratory-derived and naturally-selected antibiotic resistant mutants, suggesting the antibiotic induced production of ROS is not universal and varies according to the genetic background of the strains [ 38 ].…”
Section: Resultsmentioning
confidence: 99%